WE ARE CAPABLE OF FACING THE CHALLENGES AHEAD INCLUDING GENERATING OWN INCOME - PROF LKT - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 26 December 2015 Universiti Sains Malaysia (USM) needs to brace for the many challenges in 2016 and the years ahead including in the area of generating own income.